The Phenomenon of Insecurity Social Media Users on Instagram Among Students At University of Swadaya Gunung Jati - Sofhia Asni Shania; Farida Nurfalah; Yanto Heryanto (Siber Nusantara Research, 2026)
The phenomenon of insecurity is increasingly experienced by college students alongside the growing use of social media, particularly Instagram. This study aims to identify the factors contributing to feelings of insecurity among active Instagram users at Swadaya Gunung Jati University, as well as the efforts made to address them. This study employs a qualitative phenomenological approach using in-depth interviews with students as research informants. The results indicate that feelings of insecurity are primarily driven by internal and external factors. Internal factors include a lack of emotional support from family, unmet physiological needs, low emotional intelligence, and difficulties in expressing emotions. External factors stem mainly from Instagram use, particularly regarding self-presentation, social presence, and a tendency toward social comparison. Early-stage interactions on social media have not been able to meet the need for social acceptance and support, thereby causing feelings of insecurity. This study also found that students make various efforts to overcome feelings of insecurity through self-reflection, self-acceptance, and managing their use of social media.